Penerapan Metode Simple Multi-Attribute Rating Technique untuk Pemilihan Lokasi Kos Terbaik di Kawasan UIN Suska Riau - Riszki Fadillah; Putri Anglenia; Astia Weni Syaputri; Mustakim Mustakim (Jurnal Ilmiah Rekayasa dan Manajemen Sistem Informasi, 2019)
Information needs against boarding houses and the current location are important, to find the location of the boarding houses that fit the desires and confused to its decision because of the many boarding houses that are available. This research will be conducted on the application of the method of a decision support system to select the location of the area's finest boarding houses UIN Suska Riau using a few street names as alternative and criteria that have been tailored to their needs. To help someone chose the location of the boarding houses, then built the expected decision support systems can help a person to choose the location of the boarding houses. The methods used in decision support system is a method of Simple Multi-Attribute Rating Technique (SMART) to select or specify the location of the boarding houses the best there is in the region of UIN Suska Riau. From the results of the completion of a method using SMART obtained the rank of 20 alternatives with rank one in the street Mustamindo with a value of utilities 0.64, in the alley of Iman value utilities is 0.63, and so on until the 20th rank. After the implemented decision support system, further Testing is performed by using the user Acceptance Testing results obtained then the average response i.e. 97%, in accordance with the reality of the expected response. Kata kunci: Boarding House, Decision Support System, Simple Multi-Attribute Rating Technique, SMART.